Acute Thermoregulatory and Cardiovascular Response to Submaximal Exercise in People With Multiple Sclerosis - Gervasoni, Elisa; Bertoni, Rita; Anastasi, Denise; Solaro, Claudio; Di Giovanni, Rachele; Grange, Erica; Gunga, Hanns-Christian; Rovaris, Marco; Cattaneo, Davide; Maggioni, Martina Anna; Merati, Giampiero (Frontiers in Immunology, 2022)
Background. Heat sensitivity occurs in a high percentage of people with multiple sclerosis (PwMS), in response to environmental or exercise-induced increase in body temperature. However, the kinetic and magnitude of adaptation of the internal load and of the core body temperature (CBT) to a submaximal continuous exercise has been poorly addressed in PwMS; this may be relevant for the brief exercise bouts usually occurring in normal daily life. The aim of this work was to evaluate whether multiple sclerosis influences the acute adaptation of the internal load, the CBT and the perceptual load in response to a constant submaximal work step. Methods. CBT has been continuously monitored (0.5 Hz) by a validated wearable heat-flux sensor and electrocardiography was recorded (250 Hz) by a wearable device during a standard 6-minute walk test (6MWT) in 14 PwMS (EDSS, 4.7±1.2; disease duration: 13.0±10.2 years; m±SD) and 14 age, sex and BMI-matched healthy subjects (HS). The rate of perceived exertion (RPE) of the lower limbs was assessed during the 6MWT by the Borg scale (6-20). Results. As expected, PwMS walked a significantly shorter distance (361±98 m) than the HS group (613±62 m, p<0.001 vs PwMS). However, the kinetics of adaptation of CBT and the magnitude of CBT change from baseline did not differ between groups. Similarly, heart rate (HR) kinetics and HR change from baseline were comparable between groups during the 6MWT. Finally, lower limbs RPE gradually increased during the exercise test, but without significant differences between groups. Conclusion. The internal load, the metabolic heat production, and the perceptive load due to a standard submaximal walking exercise seems to be preserved in PwMS, suggesting a comparable acute heat production and dissipation during exercise. Therefore, it is unlikely that the different distance achieved during the 6MWT may be caused by altered thermoregulatory responses to exercise. Rather, this appears to be a consequence of the known increased energy cost of locomotion in PwMS.